2022
DOI: 10.1186/s12885-022-09180-5
|View full text |Cite
|
Sign up to set email alerts
|

High expression of S100A2 predicts poor prognosis in patients with endometrial carcinoma

Abstract: Background S100A2, a member of the S100 protein family, is abnormally expressed and plays a vital role in multiple cancers. However, little is known about the clinical significance of S100A2 in endometrial carcinoma. Methods Clinicopathological data were obtained from The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx), Gene Expression Omnibus (GEO), and Clinical Proteomic Tumor Analysis Consortium (CPTAC). First, the expression and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…For the IL-17 levels in serum, Brooks et al (44) reported no significant difference between EC patients and women without cancer, but this study has an obvious limitation of sample size that it only included 12 EC patients and 10 controls. By the way, it is worth noting that IL-17 signaling pathway was upregulated and enriched in EC supported by recent studies (92)(93)(94)(95). Besides, the serum level of IL-3 showed no difference between EC patients and healthy controls (96).…”
Section: The Il-10 Familysupporting
confidence: 67%
“…For the IL-17 levels in serum, Brooks et al (44) reported no significant difference between EC patients and women without cancer, but this study has an obvious limitation of sample size that it only included 12 EC patients and 10 controls. By the way, it is worth noting that IL-17 signaling pathway was upregulated and enriched in EC supported by recent studies (92)(93)(94)(95). Besides, the serum level of IL-3 showed no difference between EC patients and healthy controls (96).…”
Section: The Il-10 Familysupporting
confidence: 67%
“…Enriched pathways were determined using Gene Ontology (GO) [ 21 , 22 ], KEGG [ 23 25 ], and GSEA [ 26 , 27 ]. In the KEGG analysis, genes were determined to be differentially expressed based on a log2 fold-change of > 1.0 and an adjusted P -value < 0.05 ( www.kegg.jp/kegg/kegg1.html ), as previously reported [ 28 ]. “GSEA is a computational method that determines whether an a priori defined set of genes shows statistically significant, concordant differences between two biological states” [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…S100A2 expression is upregulated in endometrial carcinoma tissues in vivo [ 70 ]. Patients with endometrial carcinoma with high S100A2 expression exhibit poor overall survival and disease-specific survival in vivo [ 70 ].…”
Section: Gynecologic Cancersmentioning
confidence: 99%